Using an arithmetic sequence, it is found that the 35th value of the sequence is given by: [tex]a_{35} = 1[/tex].
In an arithmetic sequence, the difference between consecutive terms is always the same, called common difference d.
The nth term of an arithmetic sequence is given by:
[tex]a_n = a_1 + (n - 1)d[/tex]
In which [tex]a_1[/tex] is the first term.
Considering that we have the mth term as reference, the nth term is also given as follows:
[tex]a_n = a_m + (n - m)d[/tex]
In this problem, we have that:
[tex]a_{23} = \frac{2}{3}, a_{53} = \frac{3}{2}[/tex].
Hence:
[tex]a_n = a_m + (n - m)d[/tex]
[tex]a_{53} = a_{23} + (53 - 23)d[/tex]
[tex]30d = \frac{3}{2} - \frac{2}{3}[/tex]
[tex]30d = \frac{9 - 4}{6}[/tex]
[tex]30d = \frac{5}{6}[/tex]
[tex]d = \frac{1}{36}[/tex]
Then the 35th term is:
[tex]a_{35} = a_{23} + 12d = \frac{2}{3} + 12\frac{1}{36} = \frac{2}{3} + \frac{1}{3} = 1[/tex]
More can be learned about arithmetic sequences at https://brainly.com/question/6561461
#SPJ1